Analytics for Leaders : A Performance Measurement System for Business Success - Fisher, N. I. (Cambridge : Cambridge University Press, 2013)
Analytics for Leaders provides a concise, readable account of a complete system of performance measurement for an enterprise. Based on over twenty years of research and development, the system is designed to provide people at all levels with the quantitative information they need to do their jobs: board members to exercise due diligence about all facets of the business, leaders to decide where to focus attention next, and people to carry out their work well. For senior officers, chapter openers provide quick overviews about the overall approach to a particular stakeholder group and how to connect overall performance measures to business impact. For MBA students, extensive supporting notes and references provide in-depth understanding. For researchers and practitioners, a generic statistical approach is described to encourage new ways of tackling performance measurement issues. The book is relevant to all types of enterprise, large or small, public or private, academic or governmental.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Performance; Organizational effectiveness